Barriers and responses to the disclosure of non-suicidal self-injury: a thematic analysis. Issue 2 (2nd April 2020) - Rosenrot, Shaina A.; Lewis, Stephen P.
ABSTRACT: Non-suicidal self-injury (NSSI) is a prevalent behaviour among youth and young adults, yet little is known about their NSSI disclosure experiences. Disclosure of NSSI may have important implications for accessing treatment and eliciting support from family and friends; it may also highlight where efforts are needed to combat potential barriers (e.g. shame). This study sought to better understand the factors that facilitate and discourage NSSI disclosure in a sample of undergraduate students as well as gather a richer understanding of young adults' experiences disclosing NSSI. To do this, a thematic analysis of interview transcripts with 17 students (16 women and 1 man) was conducted. Themes related to barriers to disclosure (shame, concern about others) and disclosure recipients' responses (silence/avoidance, understanding) were explored. Results underscored the central role of shame in NSSI disclosures, both as an experience impacting the difficulty and likelihood of disclosure and as a potential consequence of receiving avoidant responses to disclosure. Among the clinical implications discussed is the import of initiatives to reduce NSSI stigma and foster supportive and understanding responses to NSSI disclosures.